Simply brilliant : the common-sense guide to success at work - O'Connell, Fergus (Pearson, 2012)
An astonishing number of intelligent people struggle to find solutions to the complex, varied and often frustrating problems faced in day to day work. Whether it's a major project or a minor quibble, a short dose of Fergus O'Connell's advice gives you the tools to tackle problems head-on.